Varying the expression pattern of the strigolactone receptor gene DAD2 results in phenotypes distinct from both wild type and knockout mutants - Drummond, Revel S. M.; Lee, Hui Wen; Luo, Zhiwei; Dakin, Jack F.; Janssen, Bart J.; Snowden, Kimberley C. (Frontiers in Plant Science, 2023)
The action of the petunia strigolactone (SL) hormone receptor DAD2 is dependent not only on its interaction with the PhMAX2A and PhD53A proteins, but also on its expression patterns within the plant. Previously, in a yeast-2-hybrid system, we showed that a series of a single and double amino acid mutants of DAD2 had altered interactions with these binding partners. In this study, we tested the mutants in two plant systems, Arabidopsis and petunia. Testing in Arabidopsis was enabled by creating a CRISPR-Cas9 knockout mutant of the Arabidopsis strigolactone receptor (AtD14). We produced SL receptor activity in both systems using wild type and mutant genes; however, the mutants had functions largely indistinguishable from those of the wild type. The expression of the wild type DAD2 from the CaMV 35S promoter in dad2 petunia produced plants neither quite like the dad2 mutant nor the V26 wild type. These plants had greater height and leaf size although branch number and the plant shape remained more like those of the mutant. These traits may be valuable in the context of a restricted area growing system such as controlled environment agriculture.